Underpricing, Institutional Ownership and Liquidity Stock of IPO Companies in Indonesia - Achmad, Immam Nur; Witiastuti, Rini Setyo (Management Analysis Journal, 2018)
The aim of this study is to explain and describe influence  of underpricing and institutional ownership on the liquidity. Sample of this study is 86 companies which conduct IPO in period 2012-2016. Analitycal technique used is multiple linear analysis. The data used in the form of trading data for 20 days then taken on average and comes form the company’a financial statements obtained from the Indonesia Stock Exchange. The results showed that Underpricing has a significant positive effect on liquidity. Institutional ownership is negatively insignificant to liquidity.